Organizational Culture and Readiness for Change in German pediatric outpatient centres. (13th November 2019) - Georg, S; Görig, T; Eichinger, M; Hoffmann, D; Urschitz, M S; De Bock, F
Abstract: Background: Organizational readiness for implementing change (ORIC) is presumed key for successful change in healthcare settings. At the same time, ORIC is theorized to depend on cultural and other factors of the organizational context. Within the process evaluation of the PART-CHILD intervention in interdisciplinary pediatric outpatient centres (IPOC) for children with chronic health conditions in Germany, we assessed to what extent ORIC is associated with organizational culture and further contextual factors. Methods: In 2019 data was collected from health care professionals in 12 IPOC, using a questionnaire comprising subjectively perceived ORIC (measure: ORIC, 5-point Likert scale), the organization's culture (measure: Competing Values Framework, four domains: Group, Developmental, Rational, and Hierarchical Culture) and further contextual factors (e.g., size of the facility, number of patients per year). Results: In all, responses from 206 health care professionals were included in the analyses (response rate: 47%; preliminary results). Analyses show a moderate ORIC (3, 4; SD = 0, 6), positively associated with Group Culture (r2=0, 178, p = 0, 01) and negatively associated with Rational Culture (r2=-0, 273, p < 0, 001). We found no correlations between ORIC and Developmental or Hierarchical Culture. In congress presentation we report to what extent ORIC depends on further contextual factors (e.g., size of the facility, patients' demographic characteristics). Discussion: IPOC with a strong Group Culture show a higher ORIC than those with prevailing Rational Culture. To potentially increase effective implementation of interventions in healthcare facilities in future, a preceding evaluation of the organizational culture might be valuable. Thereby, settings with prevailing Rational Culture could be identified at an early stage and receive additional implementation support, e.g. through enhancing the Group Culture among the health care professionals on-site (e.g, executive coaching). Key messages: Both organizational readiness for implementing change and organizational culture are presumed to be important for implementing change in healthcare facilities' routine care. Assessing both constructs prior to implementing a costly intervention with demanding change processes within healthcare settings could be valuable.